The Politics of Voter Suppression : Defending and Expanding Americans' Right to Vote - Wang, Tova Andrea; Nittoli, Janice (Book collections on Project MUSE., 2016)
This text assesses actual practices at the polls and re-engages with debates about voter suppression tactics such as requiring specific forms of identification. The author examines the history of how US election reforms have been manipulated for partisan advantage and establishes a new framework for analyzing laws and policies.